Cobertura vacinal na infância e mortalidade por doenças imunopreveníveis no Maranhão - Batista, Márcia Regina Souza (2023)
Given the health situation in Brazil, which is devastating the population and causing problems for community health, the National Immunization Program was created by the Brazilian government on September 18, 1973, as an instrument for implementing Brazil's vaccination schedule. Vaccination coverage is an important indicator of children's health and the quality of care provided by health systems and services, in order to assess vaccination coverage and serve as a basis for implementing policies and programs aimed at vaccination and achieving goals. Thus, the objective of this study was to analyze the relationship between childhood vaccination coverage and mortality from vaccine-preventable diseases in the state of Maranhão in the period 2000-2022. This is an ecological study. Data collection was carried out in databases and information systems: National Immunization Program Assessment Information System (SIAPI), Notifiable Diseases Information System (SINAN), of the Unified Health System's Information Technology Department (DATASUS). For trend analysis, the Prais-Winsten autoregressive model was used, in which the independent variable was the time from 2000 to 2022, and the dependent variable was the vaccination coverage by immunobiologicals in the State of Maranhão. Initially, the logarithmic transformation of the y values was performed to reduce the heterogeneity of the variance of the residuals of the regression analysis. Subsequently, the Prise regression model was applied to estimate the average annual percentage variation. Finally, the 95% confidence intervals of the measures of variation of the average annual percentage were calculated. For the statistical analysis of the modeling of coverage and infant deaths, the STATA V16 software was developed. The results show that although coverage decreased in general for all vaccines, the main decreases occurred in the following vaccines: BCG, Hepatitis B, Meningococcus C and Polio vaccine. It was observed that these processes of decreasing coverage trends may be associated with the increasing trend of infant deaths in the state of Maranhão. The association between vaccination coverage and mortality from vaccine-preventable diseases in children under 5 years of age was significant. The areas with lower vaccination coverage coincided with those with higher mortality rates, confirming the importance of immunization in reducing deaths from preventable diseases. It is concluded that the deterioration of vaccination coverage rates may lead to an increase in deaths from vaccine-preventable diseases. This data reinforces the need for immediate intervention strategies to increase awareness and ensure access to vaccination.